2019
DOI: 10.22392/actaquatr.677175
|View full text |Cite
|
Sign up to set email alerts
|

TCSG-132 Gemi Batığı Yapay Resifinin (Gökçeada, Kuzey Ege Denizi) Biyoçeşitliliği

Abstract: Bu çalışmada, Gökçeada kıyılarında 22,4 -24,8 m derinlikleri arasında bulunan TCSG-132 isimli gemi batığı üzerindeki ve çevresindeki denizel biyolojik çeşitliliğin belirlenmesi amaçlanmıştır. Bu kapsamda Ekim 2018 -Eylül 2019 tarihleri arasında sualtında türleri tanıyabilme yeteneğine sahip dalgıçlar düzenli olarak SCUBA takımları ile dalışlar gerçekleştirmiştir. Dalışlar süresince verilerin elde edilmesinde görsel sayım teknikleri (transekt, nokta sayım, kuadrat), fotoğraf çekimleri ve video kayıtları kullanı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…(2016) and Acarlı et al . (2020) reported similar H′ values with the present study. Animals across a variety of taxa and levels of the marine food web occur around artificial reefs, ranging from invertebrates to fishes and marine mammals (Paxton et al ., 2022).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…(2016) and Acarlı et al . (2020) reported similar H′ values with the present study. Animals across a variety of taxa and levels of the marine food web occur around artificial reefs, ranging from invertebrates to fishes and marine mammals (Paxton et al ., 2022).…”
Section: Discussionsupporting
confidence: 93%
“…H ′ were rather higher than obtained values from some studies conducted on ARs in the Mediterranean Sea. While Fabi et al (2002Fabi et al ( , 2004 and Gül et al (2011) found lower H ′ values, Relini et al (2002), Özgül et al (2016) and Acarlı et al (2020) reported similar H ′ values with the present study. Animals across a variety of taxa and levels of the marine food web occur around artificial reefs, ranging from invertebrates to fishes and marine mammals (Paxton et al, 2022).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations